Race-Specific Elicitors of Cladosporium fulvum Induce Changes in Cell Morphology and the Synthesis of Ethylene and Salicylic Acid in Tomato Plants Carrying the Corresponding Cf Disease Resistance Gene. - Hammond-Kosack, K. E. (1996)
Defense responses mediated by the genetically unlinked Cf-9 and Cf-2 genes were compared with those involving no Cf gene (Cf0). Compatible tomato (Lycopersicon esculentum)-Cladosporium fulvum intercellular washing fluids were injected into tomato cotyledons, and the kinetics of responses was monitored under conditions of 70 and 98% relative humidity. The latter conditions suppressed the normal macroscopic responses. For the Cf-9-Avr9 interaction, stomatal opening was induced within 3 to 4 h and after 9 h mesophyll cell death commenced. A burst of ethylene production occurred between 9 and 12.5 h and remained elevated. Free salicylic acid levels increased after 12 h, peaked at 24 h, and thereafter declined. For the Cf-2-Avr2 interaction, stomata became plugged after 8 h, and salicylic acid and ethylene levels increased by 12 and 18 h, respectively, and thereafter declined. Host cell death commenced around vascular tissue by 24 h. Cell death in both incompatible interactions was frequently preceded by cell enlargement. For Cf0-injected plants, no significant responses were detected. High humidity delayed and reduced the Cf-Avr-gene-dependent cell death and ethylene synthesis, whereas induced salicylic acid levels were unaffected for Cf-2-Avr2 and reduced in magnitude only for Cf-9-Avr9.